2020
DOI: 10.1002/uog.21939
|View full text |Cite|
|
Sign up to set email alerts
|

Value of first‐trimester ultrasound in prediction of third‐trimester sonographic stage of placenta accreta spectrum disorder and surgical outcome

Abstract: Objectives To explore whether early first‐trimester ultrasound can predict the third‐trimester sonographic stage of placenta accreta spectrum (PAS) disorder and to elucidate whether combining first‐trimester ultrasound findings with the sonographic stage of PAS disorder can stratify the risk of adverse surgical outcome in women at risk for PAS disorder. Methods This was a retrospective analysis of prospectively collected data from women with placenta previa, and at least one previous Cesarean delivery (CD) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 41 publications
0
34
0
1
Order By: Relevance
“…Surgical treatment of CSP may affect the integrity of the anterior uterine wall and may sometimes end up in unplanned hysterectomy, especially in those cases presenting with severe life‐threatening symptoms, thus affecting the future fertility of these women. Conversely, non‐surgical treatment may lead to the incomplete removal of the CSP and the persistence of the cesarean scar, thus predisposing to a recurrent CSP 1‐5 . In the present systematic review, CSP recurred in 17% of women with a prior CSP, thus highlighting the need for an early ultrasound assessment during the first trimester of pregnancy to rule out CSP.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Surgical treatment of CSP may affect the integrity of the anterior uterine wall and may sometimes end up in unplanned hysterectomy, especially in those cases presenting with severe life‐threatening symptoms, thus affecting the future fertility of these women. Conversely, non‐surgical treatment may lead to the incomplete removal of the CSP and the persistence of the cesarean scar, thus predisposing to a recurrent CSP 1‐5 . In the present systematic review, CSP recurred in 17% of women with a prior CSP, thus highlighting the need for an early ultrasound assessment during the first trimester of pregnancy to rule out CSP.…”
Section: Discussionmentioning
confidence: 79%
“…Women with CSP are at increased risk of uterine rupture and PAS, due to the anatomical weakness of the myometrium and the presence of a prior scar. This may partially explain the high incidence of uterine rupture and PAS observed in pregnancies affected by a prior CSP and highlights the need for a thorough follow up throughout pregnancy to detect these anomalies in time 1‐5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent retrospective analysis of prospectively collected data from women with placenta previa and at least one previous cesarean delivery or uterine surgery reported that early first-trimester (5–7 weeks’ gestation) sonographic assessment of pregnancies with previous cesarean delivery can predict the ultrasound stage of placenta accreta spectrum disorder [ 14 ]. Three sonographic markers for first-trimester assessment of CSP were analyzed: Already mentioned crossover sign (reported by Cali et al), implantation of the gestational sac on the scar vs. in the niche of the cesarean scar (reported by Kaelin Agten et al), and position of the center of the gestational sac below vs. above the midline of the uterus (reported by Timor-Tritsch et al).…”
Section: Discussionmentioning
confidence: 99%
“…The COS is a new sonographic sign that indicates the relationship between the gestational sac of the CSP, anterior uterine wall and caesarean scar was used 7 . Previous studies 8,9 have reported that the crossover sign (COS) is independent risk factors for severe bleeding in CSP. The COS can predict the risk of adverse outcomes in CSP patients.…”
Section: Introductionmentioning
confidence: 99%